Design and Evaluation of a Simulation for Pediatric Dentistry in Virtual Worlds - Papadopoulos, Lazaros; Pentzou, Afroditi-Evaggelia; Louloudiadis, Konstantinos; Tsiatsos, Thrasyvoulos-Konstantinos (JMIR Publications, 2013)
BackgroundThree-dimensional virtual worlds are becoming very popular among educators in the medical field. Virtual clinics and patients are already used for case study and role play in both undergraduate and continuing education levels. Dental education can also take advantage of the virtual world's pedagogical features in order to give students the opportunity to interact with virtual patients (VPs) and practice in treatment planning. ObjectiveThe objective of this study was to design and evaluate a virtual patient as a supplemental teaching tool for pediatric dentistry. MethodsA child VP, called Erietta, was created by utilizing the programming and building tools that online virtual worlds offer. The case is about an eight-year old girl visiting the dentist with her mother for the first time. Communication techniques such as Tell-Show-Do and parents' interference management were the basic elements of the educational scenario on which the VP was based. An evaluation of the simulation was made by 103 dental students in their fourth year of study. Two groups were formed: an experimental group which was exposed to the simulation (n=52) and a control group which did not receive the simulation (n=51). At the end, both groups were asked to complete a knowledge questionnaire and the results were compared. ResultsA statistically significant difference between the two groups was found by applying a t test for independent samples (P<.001), showing a positive learning effect from the VP. The majority of the participants evaluated the aspects of the simulation very positively while 69% (36/52) of the simulation group expressed their preference for using this module as an additional teaching tool. ConclusionsThis study demonstrated that a pediatric dentistry VP built in a virtual world offers significant learning potential when used as a supplement to the traditional teaching techniques.